Uji Aktivitas Antibakteri Asap Cair Daun Mangga Kuweni (Mangifera odorata) terhadap Propionibacterium acnes: Antibacterial Activity Test of Liquid Smoked Leaves of Mango Kuweni (Mangifera odorata) against Propionibacterium acnes - Bagaskara Adi Nugroho; Adam M. Ramadhan; Novita Eka Kartab Putri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Liquid smoke is the result of condensation or vapor condensation produced by direct or indirect combustion of materials containing cellulose, lignin, hemicellulose, and other carbon compounds. The function of liquid smoke is as an antioxidant and antibacterial. The purpose of this study was to determine the percent yield obtained, the secondary metabolites contained in the liquid smoke, and the bacterial inhibitory activity of the liquid smoke of the leaves of Mango Kuweni (Mangifera odorata). The method used in this research is pyrolysis and distillation for the manufacture of liquid smoke. As for the antibacterial test using the agar diffusion method with paper discs. The results showed that the yield obtained from the manufacture of liquid smoke grade 3 was 26.87%, grade 2 was 17.91%, and grade 1 was 14.33%. Secondary metabolites contained in the liquid smoke of the leaves of Mango Kuweni (Mangifera odorata) are Flavonoids, Alkaloids, and Phenols. The results of antibacterial testing using the bacteria Propionibacterium acnes showed inhibitory activity of 20% concentration of 4.4 mm (weak), 30% concentration of 4.76 mm (weak), 40% concentration of 5.21 mm (weak) and positive control, namely clindamycin of 15.27 mm (strong).